Sengketa Pajak dalam Perspektif Wajib Pajak (Studi Kasus Restitusi Pajak ADHI-IBG, KSO) - Wellia Novita; Rida Rahim; Fajri Adrianto (Owner : Riset dan Jurnal Akuntansi, 2022)
Tax disputes are not as scary as most people imagine. Tax disputes are also not something that should be feared by taxpayers or other tax actors. This paper explains how a tax dispute is manifested as a difference of opinion. Differences of opinion in terms of interpreting or interpreting a tax provision and regulation. Differences in how to apply tax regulations to real business conditions occur. This tax dispute also occurred in ADHI-IBG, KSO. This research is a qualitative descriptive research. The data used in this study are SPHP data and response letters from taxpayers. From the analysis conducted, the researcher grouped the differences in views due to differences in understanding related to the enforcement of tax rules and differences in understanding of the accounting system used by companies and financial documents that became the elements that caused tax disputes to occur. This dispute has become more and more protracted and lengthy due to the inappropriate behavior of the tax examiner. The behavior raised by the tax auditor is that the tax auditor does not accept the arguments against the financial system used by the taxpayer and the rules in tax audit. The attitude of abuse of power possessed by the examiner also makes the examiner ignore and re-examine the explanation given by the taxpayer. The attitude that is also raised by the tax examiner is to refute the explanation of the taxpayer using mere assumptions, without clear data. In this condition, the taxpayer only fights for justice in the midst of the examiner's behavior that abuses power. A long process in fighting for justice must be passed. It is not a matter of material being accepted, but this is done so that similar incidents do not happen again in the future.